SMS Girl Data Insights : How Has COVID-19 Affected Support for Girls’ Education in Punjab, Pakistan? - Hasan, Amer (World Bank, Washington, DC, 2021)
This brief presents initial findings from an ongoing phone survey of families in Punjab, Pakistan designed to assess what is happening to girls’ elementary school education during COVID-19. The data used in this brief describe the experiences of 5,898 families in Punjab between August and October 2020. Data have been weighted to make the sample representative of all schools in Punjab. This brief provides information from an on-going survey. Further data is being collected and analyzed. Subsequent briefs will provide updates on these families as we learn more about their experiences. Unless otherwise noted, statistics are based on the full sample of households contacted, 90 percent of which are families with girls in grades 5-7 before the pandemic. Statistics are weighted to make the sample representative of all schools in Punjab and to allow comparisons between boys and girls.